PENGARUH GAJI DAN JUMLAH TANGGUNGAN KELUARGA TERHADAP JUMLAH KONSUMSI BURUH PT.SUKA JAYA MAKMUR-KETAPANG ( STUDI KASUS BENGKEL BESAR ) - B01112021, DWI AFRIANI AFRIANI (Jurnal Pembangunan dan Pemerataan, 2016)
ABSTRACTThis study aims to determine the effect of the salary and the number of family dependents to the number of workers' consumption PT. Suka Jaya Makmur. This research is a qualitative approach with case study method lies on the big workshop. This study uses primary data in the form of questionnaires. The analytical method used is multiple regression analysis with the least squares method or ordinary least squares (OLS). Sources of data obtained from direct interviews and questionnaires. The results showed that salaries positive and significant effect on the amount of consumption with a significance level of 0.0286 > 0.05 and the number of family dependents positive and significant effect on the amount of consumption with a significance level of 0.0045 < 0.05.Keywords: Salaries, Number of Dependents, Total Consumption